Kinetic study of the ethyl lactate synthesis from triose sugars on Sn/Al 2 O 3 catalysts - Pighin, Eduardo Andres (2017)
The reaction kinetics of the liquid-phase synthesis of ethyl lactate from dihydroxyacetone and ethanol was studied on Sn-promoted alumina catalysts. Yields of ≈70% were obtained at 353K after 7 hours of reaction. The effect of the catalyst Sn loading (1-8 wt.%) and reaction temperature (343-373K) on the reaction kinetics was investigated. The reaction is promoted by Lewis acid sites provided by surface Sn species. A kinetic model based on a pseudohomogeneous mechanism was postulated to describe the reaction network comprising a sequence of consecutive and parallel reaction steps. The kinetic rate constant associated to ethyl lactate formation increases with the number of Lewis acid sites confirming that surface Sn species participate in the kinetically relevant reaction steps. Catalysts were prepared by impregnation and characterized by N2 physisorption, X-ray diffraction, UV-vis-DRS, FTIR of pyridine and TPD of NH3..